STUDI KOMPARASI RESPON ANTIBODI PASCA VAKSINASI CLASSICAL SWINE FEVER PADA BABI LANDRACE DAN BABI LOKAL TIMOR DI KABUPATEN KUPANG, NUSA TENGGARA TIMUR - Salestin, Ledy Chehfzy; Gelolodo, Maria Aega; Tangkonda, Elisabet; Sanam, Maxs U. E.; Bili, Feny A. L. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2021)
Classical Swine Fever (CSF) is an important infectious disease caused by the CSF virus, which belongs to the Pestivirus genus from the family Flaviviridae. This disease has a high fatality rate in swine. Stamping out the disease and vaccinations aimed at forming and strengthening antibodies against CSF are proven to be effective ways of disease control and prevention. Several factors, including age, immune status, health status, nutrition, and the environment, are believed to influence the success of the immunization program. Furthermore, it is assumed that different pig breeds may have impacts on vaccination success. This study aimed to compare antibody responses after CSF vaccination in two different pig breeds, Landrace and local Timor pigs. A total of 26 pigs (13 pigs for each group) was occupied in this study. All of the pigs used in this study had never been vaccinated against CSF. Antibody titers were quantified using an ELISA test, then the data were compared using an independent t-test to assess the difference of antibody responses between Landrace and local Timor pigs. Finally, the study found no significant difference in antibody response between Landrace and local Timor pigs, with a significant value of 0.07 (P > 0.05). Therefore, it is feasible to conclude that breed does not influence antibody response following CSF vaccination.